Handbook of research on decision-making techniques in financial marketing - Dinçer, Hasan, 1982-; Yuksel, Serhat, 1983- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2020)
"This book integrates financial and marketing functions together to make sense of environment and business-related challenges. It also explores using multi criteria decision making methods for financial challenges while marketing theories are used as theoretical bases"--